HUBUNGAN KEMAMPUAN KOMUNIKASI LISAN DENGAN PERILAKU SOSIAL PADA ANAK USIA 5-6 TAHUN, di TK PEMBINA II KOTA PEKANBARU - Hannisa Febri Yolanda; Zulkifli N Zulkifli N; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to determine verbal communication skills, social behavior, the relationship between oral communication skills and social behavior of children aged 5-6 years in Kindergarten Pembina II Pekanbaru City. The location of this research will be carried out at Pembina II Kindergarten in Pekanbaru, while this research is planned to be carried out at the end of November 2022. The population and samples in this study are the same, namely 53 children aged 5-6 years in Pembina 2 Kindergarten, Kota Pekanbaru. The data collection technique used in this study is a non-test, namely the type of observation. Based on the results of data analysis and discussion, a conclusion can be drawn: the oral communication skills of children in Kindergarten Pembina II are mostly in the Developing According to Expectations (BSH) category. Most children's social behavior is included in the Developing According to Expectations (BSH) category. Based on the results of hypothesis testing, the two variables have a significant relationship. This can be seen from the results of the study where a significant value in the correlation test was obtained for 5.874 ≥ 1.701 so it can be concluded that the relationship between children's verbal communication skills and children's social behavior is significant with a significant level of 5%.Keywords: Relationship Oral Communication Ability, Social behavior